2007
DOI: 10.1038/sj.emboj.7601661
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiscs unravel the interaction between the SecYEG channel and its cytosolic partner SecA

Abstract: The translocon is a membrane-embedded protein assembly that catalyzes protein movement across membranes. The core translocon, the SecYEG complex, forms oligomers, but the protein-conducting channel is at the center of the monomer. Defining the properties of the SecYEG protomer is thus crucial to understand the underlying function of oligomerization. We report here the reconstitution of a single SecYEG complex into nano-scale lipid bilayers, termed Nanodiscs. These water-soluble particles allow one to probe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
130
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 52 publications
7
130
0
1
Order By: Relevance
“…Of the bilayer constituents, the response seems to be specific to CL and to a lesser degree PG. The results explain a number of observations specifying the requirement of acidic phospholipids in protein translocation (1)(2)(3)(4)(5)23). The inherent symmetry of CL, with two glycerol-linked PGs, might be utilized in the interaction with twin copies of SecYEG.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Of the bilayer constituents, the response seems to be specific to CL and to a lesser degree PG. The results explain a number of observations specifying the requirement of acidic phospholipids in protein translocation (1)(2)(3)(4)(5)23). The inherent symmetry of CL, with two glycerol-linked PGs, might be utilized in the interaction with twin copies of SecYEG.…”
Section: Discussionsupporting
confidence: 67%
“…In keeping with this, the bacterial protein translocation reaction, driven by the ATPase SecA through the conserved SecYEG complex, has a known requirement for acidic phospholipids (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously described the incorporation of the SecY monomer into discs using the membrane scaffold protein 1 (MSP1, referred to as Nd-Y) (23). We also reported that SecA and Syd formed a tight complex with the Nd-Y particles (23,26) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Protein translocation taking place at one SecY copy might be facilitated by the second, or translocation may strictly depend on the dimer. The question is further complicated by the dynamic dimeric state of SecA and whether one or two SecA molecules bind to the channel (22)(23)(24)(25).…”
mentioning
confidence: 99%